2017
DOI: 10.1158/0008-5472.can-17-0657
|View full text |Cite
|
Sign up to set email alerts
|

SPIN90 Depletion and Microtubule Acetylation Mediate Stromal Fibroblast Activation in Breast Cancer Progression

Abstract: Biomechanical remodeling of stroma by cancer-associated fibroblasts (CAF) in early stages of cancer is critical for cancer progression, and mechanical cues such as extracellular matrix stiffness control cell differentiation and malignant progression. However, the mechanism by which CAF activation occurs in low stiffness stroma in early stages of cancer is unclear. Here, we investigated the molecular mechanism underlying CAF regulation by SPIN90 and microtubule acetylation under conditions of mechanically soft … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…The inhibitory effects of irigenin in our in vivo mice model suggest a possible approach for overcoming limitations on the delivery of established anticancer drugs. Increased FN(+)EDA, appearing as aligned fibrils, was observed in the tumor stroma of 10 breast cancer patients in which SPIN90 downregulation was detected (You et al, ). This correlation between SPIN90 downregulation and FN(+)EDA expression suggests that FN(+)EDA contributes to the development of a stiff ECM in breast cancer stroma.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The inhibitory effects of irigenin in our in vivo mice model suggest a possible approach for overcoming limitations on the delivery of established anticancer drugs. Increased FN(+)EDA, appearing as aligned fibrils, was observed in the tumor stroma of 10 breast cancer patients in which SPIN90 downregulation was detected (You et al, ). This correlation between SPIN90 downregulation and FN(+)EDA expression suggests that FN(+)EDA contributes to the development of a stiff ECM in breast cancer stroma.…”
Section: Discussionmentioning
confidence: 99%
“…MEFs were isolated and immortalized as previously described (You et al, 2017) (Gapdh) and presented as fold change relative to the indicated controls. The following primers were used for RT-PCR and qRT-PCR.…”
Section: Cell Culturementioning
confidence: 99%
See 3 more Smart Citations